Data superstream : data lakes and warehouses. (O'Reilly Media, Inc., 2022)
Storing, processing, and moving data in the cloud efficiently and cost-effectively is a must for working with today's enormous datasets. These expert-led sessions will help you gain insight into how to increase the scalability, speed, and availability of your data, along with best practices for utilizing your data warehouse, data lake, or data lakehouse. About the Data Superstream Series: This three-part Superstream series is designed to help your organization maximize the business impact of your data. Each day covers different topics, with unique sessions lasting no more than four hours. And they're packed with insights from key innovators and the latest tools and technologies to help you stay ahead of it all. What you'll learn and how you can apply it Get an overview of the latest technologies for storing and managing your data Learn cutting-edge strategies for optimizing and deploying your cloud data lake Understand how to implement access control to maintain data privacy in your cloud data warehouse Find out how to utilize the lakehouse architecture to support ML and AI applications Discover the benefits of a data mesh approach for addressing data ownership challenges in your organization This recording of a live event is for you because... You're a data or software engineer or solution architect interested in learning about the latest trends in storing, processing, and managing data. You want to improve the scalability, speed, and availability of your data. You want to better understand the systems that you already use and learn how to take full advantage of their capabilities. Recommended follow-up: Read The Enterprise Big Data Lake (book) Read Delta Lake: The Definitive Guide (early release book) Take Data Mesh in Practice (live online training course with Max Schultze and Arif Wider) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.